To give or not to give professional services to non-paying clients: Professionals' giving backstory. Issue 3 (15th June 2015) - McColl-Kennedy, Janet R.; Patterson, Paul; Brady, Michael K.; Cheung, Lilliemay; Nguyen, Doan
Abstract : Purpose: – The purpose of this paper is to explicate professionals' giving backstory, identifying what motivates and hinders professionals' undertaking of pro bono service activities. Examples are provided of different pro bono giving styles, as professionals struggle to resolve inter-institutional tensions, thus addressing this little understood yet vital form of giving, and meeting an important research priority. Design/methodology/approach: – Using a discovery-oriented grounded theory approach, this paper draws on narratives from interviews with 31 professionals to explicate, from the professional's point of view, the backstory of pro bono service. Findings: – The authors provide an integrative institutional logics-based framework for understanding the backstory to professionals' giving. Three distinct pro bono giving styles are revealed: first, an individual logic (self-centric), an "I" logic; second, an organizational logic (organization-centric), "We" logic; and third, a societal "All" logic (where the greater good to society in general is the dominant logic). The paper concludes with recommendations for how professionals and professional service firms (PSFs) can better align their pro bono giving styles with non-paying not-for-profit clients for multi-party benefit. Originality/value: – The originality of this research lies in addressing an important yet little understood form of giving through delving into the backstory to pro bono service. First, the paper theorizes the characteristics of a formerly unarticulated form of giving, distinguishing it from individual-to-individual close consumer gifting, individual to organizational charitable giving, sponsorship, and volunteering. Second, the different inter-institutional logics of pro bono giving are identified, with three main pro bono giving styles uncovered. Third, the authors link professional services theory, theoretical perspectives from giving, and institutional logics theory to develop an integrated framework to explain service professionals' pro bono activities. Furthermore, a compelling agenda for future research is provided to guide future work.